ENDOTHELIAL CELLS PRODUCE PLATELET ACTIVATING FACTOR WHICH PRIMES NEUTROPHILS TO RELEASE OXIDANT PRODUCTS - Wickham, N W R; Vercellotti, G M; Yin, H Q; Jacob, H S; Moldow, C F (Thrombosis and Haemostasis, 1987)
Thrombin (THR) is generated during ARDS, sepsis and DIC. We wondered whether it might augment PMN/endothelial cell (EC) interaction and hence amplify EC damage by inducing platelet activating factor (PAF) (JCI 76:2235-2246;1985). To examine further this premise and the mechanisms involved, we measured intracel1ular calcium (Ca1) in human EC (grown on glass cover slips), in a scanning spectrof1uorometer at 37°C after loading with FURA 2 (4μM). Resting Ca1 was 148±22 nM (Mean±SEM) which increased following THR 0.5u/ml to 458±160 nM at 30s, peaking after 1 min at 559±176 nM, and returning to 273±42 nM by 5 min. Phosphatidyl inositol (PI) turnover was assessed in 3H-myoinositol-loaded EC using water-soluble extracts separated by Dowex anion exchange chromatography. Within 30s of THR (lu/ml) stimulation, PI turnover markedly increased, with production of inositol bi- and tri-phosphates showing a >5 fold rise. Associated with these perturbations, THR-treated EC monolayers enhanced O2- generation by FMLP(10™7)-stimulated PMNs (basal levels of 5.73±0.68 O2-/15 min/106 PMN rising to 8.01±0.85 nM (p<0.05)); moreover this enhancement could be completely inhibited with a newly described PAF antagonist BN 52021. PAF production is dependent upon phosphorylation of an acetyl transferase, and Ca1 flux and PI hydrolysis are events known to be associated with protein kinase activation. THR-EC stimulation would seem, therefore, to initiate a sequence of events involving PMN/EC 'cross-talk' leading to contact activation of marginated PMNs by EC-derived PAF. This is an example of a novel paracrine response, and is consistent with our data showing the potent priming effect of PAF on PMN oxidant responses (Blood 68:88A; 1986) and provides evidence for a previously unsuspected pathway that promotes PMN oxidant-mediated EC injury during sepsis or other THR-generating disorders.